2021
DOI: 10.25073/2525-2445/vnufs.4665
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Lexical Cohesive Devices in Reading Texts in the Textbook Tiếng Anh 10 Published by Vietnam Education Publishing House

Abstract: The research examines the lexical cohesive devices in the textbook Tiếng Anh 10 published by Vietnam Education Publishing House. This study employs a documentary method of analysis to answer the research question. In particular, Halliday and Hasan’s framework of cohesion in discourse (1976) was adopted to investigate ten reading texts in the reading section. The findings show that in terms of reiteration, repetition is the most frequently used device in all reading texts to make the reading semantically relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…This type of repetition also creates a monotonous impression in the presentation of the materials, so the reading materials failed to provide adequate language enrichment for students. This finding is in line with the studies by Alotaibi (2015), Nguyen &Dong (2021), andSari et al (2022), which concluded that repetition tends to be the dominant type of lexical cohesion in textbooks. The use of excessive repetition, compared to other types of lexical cohesion, shows that the book's authors ignore the principles of coherence in compiling material (Alotaibi, 2015;Nguyen & Dong, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This type of repetition also creates a monotonous impression in the presentation of the materials, so the reading materials failed to provide adequate language enrichment for students. This finding is in line with the studies by Alotaibi (2015), Nguyen &Dong (2021), andSari et al (2022), which concluded that repetition tends to be the dominant type of lexical cohesion in textbooks. The use of excessive repetition, compared to other types of lexical cohesion, shows that the book's authors ignore the principles of coherence in compiling material (Alotaibi, 2015;Nguyen & Dong, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…First, lexical cohesion significantly makes it easier for students to understand reading text materials (Mandarani et al, 2022;Zahrudhin Verdiansyah et al, 2019). Second, lexical cohesion can expand students' vocabulary by displaying various ways to express the same meaning (Faizin et al, 2023;Nguyen & Dong, 2021;Zhao, 2021). Third, lexical cohesion can organize the flow of information so that the reading text displayed is coherent and systematic (Díaz, 2021;Muttaqin, 2019;Nguyen & Dong, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors were collected through interviews for family history, cranium injury history, and toxic exposure. Relieving factors included medication history of using NSAID and using estrogen replacement therapy in postmenopausal women [12].…”
Section: Data Collection and Intervention Methodsmentioning
confidence: 99%